Unlocking Andean sigmodontine diversity: five new species of Chilomys (Rodentia: Cricetidae) from the montane forests of Ecuador - Brito, Jorge (2022)
The Andean cloud forests of Ecuador are home to several endemic mammals. Members of the Thomasomyini rodents are well represented in the Andes, with Thomasomys being the largest genus (47 species) of the subfamily Sigmodontinae. Within this tribe, however, there are genera that have escaped a taxonomic revision, and Chilomys Thomas, 1897, constitutes a paradigmatic example of these “forgotten” Andean cricetids. Described more than a century ago, current knowledge of this externally unmistakable montane rodent is very limited, and doubts persist as to whether or not it is monotypic. After several years of field efforts in Ecuador, a considerable quantity of specimens of Chilomys were collected from various localities representing both Andean chains. Based on an extensive genetic survey of the obtained material, we can demonstrate that what is currently treated as C. instans in Ecuador is a complex comprising at least five new species which are described in this paper. In addition, based on these noteworthy new evidence, we amend the generic diagnosis in detail, adding several key craniodental traits such as incisor procumbency and microdonty. These results indicate that Chilomys probably has a hidden additional diversity in large parts of the Colombian and Peruvian territories, inviting a necessary revision of the entire genus.